A Students’ Perspective on University Education and Well-Being One-Year into the COVID-19 Pandemic - Gareeb, Akira; Gavazzi, Isabella; Woodman, Natasha; Goonasekera, Chulananda; Lombard, Antoinette; Faruq, Mohammad Omar; Ray, Joanna; Dhanapala, Rasika; Sandarenu, Sadhani; Mahjabeen, Mosarrat; Hashmi, Seema; Kottahachchi, Darshana; et al. (International Journal of Medical Students, 2023)
We report university student perspectives on COVID-19 impact on education, general health and well-being, one year into the pandemic. A ‘low risk’ questionnaire with modified General Health (GHQ-28) and Anxiety Disorder (GAD-7) instruments was shared with students via an email link over a 4-week period. 725 students responded from five countries. Half of the students reported significant general health difficulties and more than ten per cent experienced a severe state of generalised anxiety disorder. The virtual learning techniques adopted during the pandemic were welcomed by students but many were frustrated by the poor quality teaching material, poor scheduling of virtual sessions with inadequate spacing and assessments not being truly representative of what was taught. Digital poverty due to inadequacies in hardware, software compatibility and connectivity were major hindrances to virtual learning. Universities should urgently modify the virtual training methods and enhance mental health and wellbeing support before disaster strikes.